Autoantibodies to Chemokines and Cytokines Participate in the Regulation of Cancer and Autoimmunity - Karin, Nathan (Frontiers in Immunology, 2018)
We have previously shown that predominant expression of key inflammatory cytokines and chemokines at autoimmune sites or tumor sites induces loss of B cells tolerance, resulting in autoantibody production against the dominant cytokine/chemokine that is largely expressed at these sites. These autoantibodies are high affinity neutralizing antibodies. Based on animal models studies we suggested that they participate in the regulation of cancer and autoimmunity, albeit at the level of their production cannot entirely prevent the development and progression of these diseases. We have therefore named this selective breakdown of tolerance as "Beneficial Autoimmunity". Despite its beneficial outcome this process is likely to be stochastic and not directed by a deterministic mechanism, and is likely to be associated with the dominant expression of these inflammatory mediators at sites that are partially immune privileged. A recent study conducted on AIRE (autoimmune regulator) deficient patients reported that in human this type of breakdown of B cell tolerance is T cell-dependent. This explains, in part, why the response is highly restricted, and includes high affinity antibodies. The current mini-review explores this subject from different complementary perspectives. It also discusses three optional translational aspects: amplification of autoantibody production as a therapeutic approach, development of autoantibody based diagnostic tools, and the use of B cells from donors that produce these autoantibodies for the development of high affinity human monoclonal antibodies.